Demographic Change in Japan and the EU : Comparative Perspectives - Coulmas, Florian; Godzik, Maren; Oda, Akiko; Ronald, Richard; Schad-Seifert, Annette; Schad-Seifert, Annette; Shimada, Shingo; Shimada, Shingo; Tagsold, Christian; Wagner, Cosima; Yamada, Atsuhiro (düsseldorf university press, 2010)
This volume contains selected papers of the 2008 annual conference of the German Association for Social Science Research on Japan (Vereinigung für sozialwissenschaftliche Japanforschung e.V. - VSJF). The academic meeting has addressed the issue of demographic change in Japan in comparison to the social developments of ageing in Germany and other member states of the European Union. The conference was organized by the Institute for Modern Japanese Studies at Heinrich-Heine-University of Duesseldorf and took place at the Mutter Haus in Kaiserswerth (an ancient part of Duesseldorf). Speakers from Germany, England, Japan and the Netherlands presented their papers in four sessions on the topics "Demographic Trends and Social Analysis", "Family and Welfare Policies", "Ageing Society and the Organization of Households" and "Demographic Change and the Economy". Central to all transnational and national studies on demographic change is the question of how societies can be reconstructed and be made adaptive to these changes in order to survive as solidarity communities. The authors of this volume attend to this question by discussing on recent trends of social and economic restructuring and giving insight into new research developments such as in the area of households and housing, family care work, medical insurance, robot technology or the employment sector.